Regional Disparities in North Kalimantan: A Decade after Territorial Split - Rahman, Syahrir; Saifudin, Al Muhammad Fatahuddin; Azizah, Zumrotul Nur (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2024)
Territorial split is one of the Government of Indonesia’s strategies to address regional disparities and promote equitable development along with effective government administration nationwide. Various studies on the impact of territorial splits in the new autonomous regions have indicated that these measures have achieved limited success, particularly during the initial period following the implementation of the Regional Autonomy policy in the early 2000s. North Kalimantan, which was established in 2012 as one of Indonesia's youngest provinces, may present different outcomes compared to other autonomous regions formed during the early stages of these policies. This study aims to analyze the economic development and regional disparities indicators in North Kalimantan before and after the 2012 territorial split. This research utilizes data from the Central Bureau of Statistics of the Republic of Indonesia, including national, provincial, and regency/city levels, aiming to analyze economic development trends from pre- to post-slit 2012, as measured by Gross Regional Domestic Product (GRDP), GRDP per capita, Gini Index, Williamson Index, and Klassen Typology. The findings show that economic development indicators in North Kalimantan have improved following the territorial split. Regional disparities indicators such as the Williamson Index and Klassen Typology Analysis also show an improved situation in North Kalimantan post-split, making it one of the regions that has successfully grown and thrived well after the territorial split. The strong economic potential of North Kalimantan before the territorial split may have played a role in maintaining its economy in the post-split period.